Self-reactive T cells induce and perpetuate chronic relapsing arthritis - Tuncel, Jonatan (Arthritis Res Ther, 2020)
BACKGROUND: CD4(+) T cells play a central role during the early stages of rheumatoid arthritis (RA), but to which extent they are required for the perpetuation of the disease is still not fully understood. The aim of the current study was to obtain conclusive evidence that T cells drive chronic relapsing arthritis. METHODS: We used the rat pristane-induced arthritis model, which accurately portrays the chronic relapsing-remitting disease course of RA, to examine the contribution of T cells to chronic arthritis. RESULTS: Rats subjected to whole-body irradiation and injected with CD4(+) T cells from lymph nodes of pristane-injected donors developed chronic arthritis that lasted for more than 4 months, whereas T cells from the spleen only induced acute disease. Thymectomy in combination with irradiation enhanced the severity of arthritis, suggesting that sustained lymphopenia promotes T cell-driven chronic inflammation in this model. The ability of T cells to induce chronic arthritis correlated with their expression of Th17-associated transcripts, and while depletion of T cells in rats with chronic PIA led to transient, albeit significant, reduction in disease, neutralization of IL-17 resulted in almost complete and sustained remission. CONCLUSION: These findings show that, once activated, self-reactive T cells can sustain inflammatory responses for extended periods of time and suggest that such responses are promoted in the presence of IL-17.